Job Stress and Employee Creativity: The mediating role of Emotional Intelligence - Naseem, Khalida (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
The obstinacy of this study is to lessen the job stress between individuals at work place by mediating the relationship through emotional intelligence. Emotional intelligence between predictor and criterion variables enhances employee well-being (creativity). Time lagged data through a self-reported questionnaire was collected from employees of Suzuki Company. Employees of Suzuki (n=150) filled the trait measure of job stress questionnaire and after three weeks’ participants completed the emotional intelligence and creativity scale. Supervisors of employees to counter check also filled up another creativity questionnaire. It is supported that employees with higher emotional level will perceive less stress and higher level of creativity. The consequences of this study for working with manufacturing industry to improve employee creativity.